Nashestvie - Room, Abram (Soviet Union : Alma-Atinskaia Kinostudiia, 1944)
Doctor Fedor Talanov returns from captivity during the WWII. Everybody, even his close relatvies, suspect Fedor of betrayal. He pays with his life for restoring his reputation.